Workshop Urgensi Pemanfaatan Media Pembelajaran Inovatif dalam Bimbingan dan Konseling Di SD - A. Hari Witono; Mansur Hakim; I Ketut Widiade; Heri Hadi Saputra; Tamy Amalia Wijaya; Heri Setiawan (Dedikasi Cendekia: Warta Pengabdian Pendidikan, 2024)
The implementation of guidance and counseling in elementary schools is the task of the class teacher. This is related to the rare availability of BK teachers or special counselors on duty in elementary schools. In fact, based on the results of observations during the implementation of the research in June-July 2022 at SD Negeri 1 Kekeri, teachers have not implemented BK services optimally. Therefore, the PGSD FKIP Universitas Mataram service team carried out community service with the title "Workshop on the Urgency of Utilizing Innovative Learning Media in Guidance and Counseling in Elementary Schools". To achieve the objectives of counseling and training as implied in the title of this community service, several methods are used, namely lectures, questions and answers or discussions and mentoring. After Community Service. After community service is completed, it is required to meet the targets, namely: (1) mandatory output in the form of one scientific paper in the form of an article in the interactive journal JIP FKIP UNRAM; and (2) additional output in the form of a statement letter on the use of IPTEK by Partners. This workshop was held on Saturday, June 22, 2024 with an interactive and practical approach. Participants were not only given theoretical materials, but also involved in discussions, simulations, and direct practice using learning media. During the workshop, some of the main materials discussed included: basic concepts of guidance and counseling at the elementary school level, the importance of utilizing innovative learning media, types of media that can be used in guidance and counseling, and ways to utilize these media effectively. The results of the pretest and posttest showed that the implementation of the workshop had a positive impact. Participants experienced an increase in understanding of all the materials presented. In addition, during the implementation of the preparation of innovative media and simulations, all participants were actively involved in creating media and practicing them